Exergy Recovery During Liquefied Natural Gas Regasification Using Methane as Working Fluid - Francesca Belfiore; Francesco Baldi; Francois Marechal (Chemical Engineering Transactions, 2018)
The increased concerns about the effect of human activities on the climate have pushed natural gas among the most obvious solutions for the transition to a low-carbon economy. The growing importance and volumes of liquefied natural gas for transportation over long distances come as a consequence of this tendency.